INVESTIGATING STAKEHOLDERS - FARMER COMPETENCIES NEXUS: EVIDENCE FROM MACTOR ANALYSIS AND ANALYTIC HIERARCHY PROCESS IN MAGELANG AND PATI REGENCIES - Widiyanti, Emi; Cahyadin, Malik; Padmaningrum, Dwiningtyas; Suminah, Suminah; Utari, Prahastiwi (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Farmer competence is the ability of farmers to think, behave, and act in managing farming businesses. The competence can involve various stakeholders (actors) and types of farmers’ competencies. Therefore, this study investigates the role of stakeholders in farmers' competencies and assesses the rank of farmers’ competencies in Magelang Regency (highland) and Pati Regency (lowland). Both regions have a significant number of millennial farmers in Central Java Province. The sample for this study was 12 people (institutions) selected using purposive sampling. They provided their perceptions of farmer competencies through in-depth interviews. The interviews were conducted during July–August 2023. MACTOR and AHP methods were applied to measure the stakeholders’ role and rank the types of farmer competencies. The findings reveal that all actors agreed on developing farmer competencies through collaboration and business partnerships. Some stakeholders have the strongest level of convergence, consisting of local government agricultural agencies, local government industry agencies, farmer communities, and the banking industries. In contrast, the strongest divergence occurs with sellers of agricultural products and local public figures. In addition, the ranking or priority of farmer competencies from the top is innovative, communication, and entrepreneurial competencies. Policy implications emphasize increasing the level of collaboration and partnership between agricultural business stakeholders and local governments to enhance and guarantee the quality of farmer competencies.